Characterizing the regulation of the Pu promoter in Acinetobacter baylyi ADP1. - Huang, W; Singer, A; Spiers, A; Preston, G; Whiteley, A (2008)
Effective gene trapping and screening requires sensory and regulatory compatibility of both host and exogenous systems. The naturally competent bacterium Acinetobacter baylyi ADP1 is able to efficiently take up and integrate exogenous DNA into the chromosome, making it an attractive host system for a wide range of metagenomic applications. To test the ability of A. baylyi ADP1 to express the XylR-regulated Pu promoter from Pseudomonas putida mt-2, we have constructed and examined an A. baylyi ADP1 strain, ADPWH-Pu-lux-xylR. The Pu promoter in ADPWH-Pu-lux-xylR was specifically induced by toluene, m-, p- and o-xylene. The substrate-induced Pu promoter was highly dependent on the growth medium: it was repressed in rich media until stationary phase, but was immediately induced in minimal medium with glucose as the sole carbon source (MMG). However, the Pu promoter was repressed in MMG when it was supplemented with 5 g l(-1) yeast extract. Further investigation showed that the Pu promoter in MMG was repressed by 0.5 g l(-1) aspartic acid or asparagine, but not repressed by glutamine. Changing the carbon/nitrogen ratios by addition of ammonia did not significantly affect the Pu promoter activity but addition of nitrate did. These results show that A. baylyi ADP1 reproduced characteristics of the XylR-regulated Pu promoter observed in its original host. It demonstrates that A. baylyi could provide an excellent genetic host for a wide range of functional metagenomic applications.